Independent Learning of the Bleended Learning Model for CPNS Training Participants - Yahman Yahman (Jurnal Prajaiswara, 2021)
This study aims to describe the tendency of learning independence of participants in the Basic Training for Candidates for Civil Servants (CPNS) in Sarolangun Regency who applies blended learning in training. The method used is qualitative descriptive. The research subjects were participants in the basic training for CPNS Sarolangun Regency in 2021 as many as two groups consisting of 18 participants. Data collection is done through direct observation of research subjects, researchers, as well as research instruments, directly observe when teaching CPNS Latsar training participants online. The results of the analysis show that the learning independence of the basic CPNS training participants is in the very good category. The indicators of learning independence include: 1) Independence from others, 2) self-confidence, 3) Behave in a disciplined manner, 4) Having a sense of responsibility, 5) Behaving on their own initiative, and 6) Exercise self-control.. The limitations of this study only describe the independence of the trainees, in the future, it is necessary to know the independence of the instructor.